Economic situation of eastern Poland and population migration movement - Michal Bernard Pietrzak; Justyna Wilk; Mariola Chrzanowska (Institute of Economic Research (IER), 2013)
The aim of this paper is to examine population migration flows in relation to the eastern Poland and its economic situation. The empirical study refers to the period 2008-2010. In the first part of the paper, the economic situations of 66 Polish sub-regions were examined. The study used the Hellwig's procedure to compare the economic situations of regions. In the second part, the amount, intensity and directions of migration flows were presented. The macroregion of eastern Poland presents the high economic disparities. The demographically active areas are ones situated in the near vicinity of provincial cities and almost the whole of the Podkarpackie province. The remaining areas of the region are characterized by high migration outflows.
Keywords: J11; O11; O15; R11; R23; 330; economic situation; internal migration; synthetic measure; ratio analysis; classification